Knowledge, Attitude and Practice Regarding Cervical Cancer Screening Among Women Attending a Teaching Hospital, Bharatpur, Chitwan - Shrestha, Smita (J Family Reprod Health, 2017)
Objective: To find out the knowledge, attitude and practice regarding cervical cancer screening among women. Materials and methods: A descriptive cross-sectional study design was used to collect data from 96 women. Each woman was selected alternately from Gynae Out-Patient Department of Teaching Hospital. Data was collected by using semi-structured interview schedule to find out knowledge and practice and Likert scale to find out the attitude regarding cervical cancer screening. Data was analyzed by using SPSS version 20.0 and interpreted in terms of descriptive and inferential statistics. Results: Out of 96 women, mean age was 38.83 ± 6.57 and 90.6% respondents followed Hinduism. More than three fourth (85.4%) were literate and 59.4% were housewife. Only 9.4% were involved in cervical cancer prevention and screening awareness programme and 2.1% had family history of cervical cancer. As per the findings, only 34.4% and 27.8% had adequate knowledge and practice respectively whereas cent percent women had favorable attitude. Only education level of women was statistically significant with level of knowledge regarding cervical cancer screening (p = 0.041). There was strong negative correlation between knowledge score and practice score regarding cervical cancer screening among women (r = -0.194). Conclusion: Considerable proportions of women have inadequate knowledge and practice regarding cervical cancer screening. Therefore cervical cancer screening health camps and awareness program should be conducted at community level for women to increase the level of knowledge and practice regarding cervical cancer screening.